Domanic Oil Shale Sediments Organic Matter and Saturating Fluids Characteristics on the Territory of the Tatarstan Republic - T. V. Grigorenko; G. G. Savostin; A. G. Kalmykov; M. S. Tikhonova; O. N. Vidishcheva; M. O. Kostyshina; M. L. Makhnutina; V. D. Storozhenko; G. A. Kalmykov; N. A. Nazimov (Georesursy)
Domanic sediments extended on the area of Tatarstan Republic in the Volga-Ural petroleum basin are the object of the investigation. They are considered to be the main source rock of the territory.   The goal is to assess their role in the oil bearing capacity of the region.   It was determined that the domanic oil shale organic matter is predominantly immature, excepting areas on the north of the South Tatar arch and on the south of the North Tatar arch with kerogen maturity of early-middle oil window. The intervals with high porosity values (2-8 %) and increased oil saturation with fluids generated by domanic oil-source rocks were determined on these areas. The comparison with the Bazhenov deposits of Western Siberia was performed to determine the conditions of kerogen high maturity formation. As structural and tectonic factors that were determined on both Western Siberia and Volga-Ural areas may promote hydrothermal exposure, hydrous pyrolysis of domanic oil shale sediments was performed to assess their contribution the organic matter transformation. The results demonstrate higher generation capacity of the domanic oil shale kerogen compared to the Bazhenov formation kerogen, with 3.5 mg HC/g TOC of gaseous products and 185 mg HC/g TOC of liquid products generated. The obtained results can be used for promising zones on the territory of the Tatarstan Republic reconnaissance.